(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, we will explore the relationship between cognitive thinking and performance on the IELTS exam, with a particular focus on the application of Bloom’s Taxonomy, a well-established framework for understanding different levels of cognitive engagement. By understanding the connection between cognitive thinking and IELTS performance, we can better understand the holistic nature of language assessment and provide valuable insights for both test-takers and educators.